Minat Beli sebagai Variabel Mediasi Pengaruh Promosi terhadap Keputusan Pembelian - Harmono, Harmono (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in economic growth, particularly in developing countries, contributing significantly to GDP and employment. In a competitive market, marketing strategies such as promotion, brand image, competitive pricing, and product innovation are crucial factors influencing consumer purchasing decisions. Signal Coffee Depok can enhance its market competitiveness by leveraging digital marketing, word-of-mouth, and attractive promotional strategies to boost consumer purchase interest. This study employs a quantitative research method with an associative approach to examine the causal relationships between promotion, purchase interest, and purchasing decisions using path analysis with SmartPLS. Data were collected through validated and reliable questionnaires, and the Sobel test was conducted to assess the mediating effect of purchase interest. The results indicate strong correlations between promotion (X) and purchase interest (Y) (r = 0.777), as well as between promotion (X) and purchasing decisions (Z) (r = 0.745), while the relationship between purchase interest (Y) and purchasing decisions (Z) is very strong (r = 0.825). Path analysis reveals that promotion directly influences purchase interest (77.7%) and purchasing decisions (26.3%), while purchase interest affects purchasing decisions by 62.1%. The indirect effect of promotion on purchasing decisions through purchase interest is 16.3%, bringing the total effect to 42.6%. The T-test and F-test confirm the significance of the relationships between variables, but the mediating effect of purchase interest in the relationship between promotion and purchasing decisions is not statistically significant. Keywords: MSMEs , Promotion , Purchasing Decision and Purchase Interest